Aktualność operatywnego modelu wykładni prawa w obliczu postmodernizmu - Szymańska, Małgorzata (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
Due to postmodernist philosophy is becoming summary increasingly popular this article concerns the validity of a legal interpretation model commonly used in modern times with regard to the postmodernist point of view. Although this problem is widely described in Western literature, in Poland, on the contrary, it is gaining popularity only among philosophers of law.The aim of the article is to present the critical approach of postmodernist philosophy to existing order and demonstrate its attitude towards interpretation of the law. It should be noted that postmodernism has no ambition of constructing its own model of legal interpretation, but comments on and reviews all that has been said on this issue in the legal theory and philosophy of law. This is due to the fact that postmodernism is hostile to all methodologies, modelling theories and theoretical constructions. On the other hand, based on the general assumptions of postmodern philosophy, a postmodern view on the interpretation of the law can be derived. The article discusses deconstructionism, hermeneutics and intertextuality as methods of creating the meaning of a legal text during interpretation, acceptable by postmodernism.The study also presents criticism of the assumption of rational legislator proposed by legal positivism. In this respect postmodernism makes a real revolution in the field of law enforcement, prioritizing the interpreter instead of the legislator, and the creation of a legal text meaning during the process of legal interpretation in place of meaning determination.
Keywords: interpretacja prawna; racjonalny ustawodawca; postmodernizm; nowoczesność; dekonstrukcjonizm